Correlation of RDW and Severity of Community Acquired Pneumonia in Children Aged Between 6 Months to 5 Years - Fatima, Zeeshina; Sami Ullah; Sami, Hafiz Ahmad (Indus Journal of Bioscience Research, 2025)
Background: Community-acquired pneumonia (CAP) is a leading cause of morbidity and mortality among children under five in developing countries. Red cell distribution width (RDW) has emerged as a potential inflammatory biomarker in a variety of diseases, but its relationship with CAP severity in children is poorly understood. Objective: To determine the relationship between RDW levels and the severity of community-acquired pneumonia in children aged 6 months to 5 years who presented to DHQ Hospital, Gujranwala. Methods: This prospective observational study included 280 children diagnosed with CAP between June and December 2024. Chronic hematological, liver, or kidney diseases were excluded. CAP severity was determined using World Health Organization (WHO) criteria. Complete blood counts were obtained upon admission. The primary result was a correlation between RDW and severity scores. Secondary outcomes included hospitalization, ICU admission, and death. Results: Of the 280 children, 220 were followed up. Out of 220, 110 (50%) had mild, 78 (35.5%) moderate, and 32 (14.5%) severe CAP. The mean RDW increased with severity: mild (13.2 ± 0.8%), moderate (14.1 ± 1.0%), and severe (15.6 ± 1.1%) (p<0.001). RDW had a significant positive correlation with the pneumonia severity index (r=0.64, p<0.001). Children with higher RDW had longer hospital stays and more ICU admissions. ROC analysis revealed that RDW ≥14.5% predicted severe CAP with 85% sensitivity and 77% specificity. Elevated RDW at admission significantly correlates with severity and negative outcomes in pediatric CAP. RDW is a low-cost, widely available biomarker that can help with early risk stratification and management in resource-limited settings. Conclusion: Elevated RDW at hospital admission is a strong, independent predictor of disease severity and adverse outcomes in children with community-acquired pneumonia. As an inexpensive and universally available parameter, RDW can be readily incorporated into routine CBC assessment to enhance early risk stratification and guide management decisions in resource-limited settings such as the DHQ Hospital Gujranwala.